Institutional reforms and educational attainment in Europe: A long run perspective - Michela Braga; Daniele Checchi; Elena Meschi (Institute for the Study of Labor (IZA), 2011)
In this paper we analyse the effects of changes in the institutional design of the educational system on school attainment. In particular, we test whether alternative reforms have increased the average educational attainment of the population and whether various deciles of the education distribution have been differentially affected. We constructed a dataset of relevant reforms occurred at the national level over the last century, and match individual information to the most likely set-up faced when individual educational choices were undertaken. Thus our identification strategy relies on temporal and geographical variations in the institutional arrangements, controlling for time/country fixed effects, as well as for confounding factors. We also explore who are the individual most likely affected by the reforms. We also group different reforms in order to ascertain the prevailing attitudes of policy makers, showing that reforms can belong to either inclusive or selective in their nature. Finally we correlate these attitudes to political coalitions prevailing in parliament, finding support to the idea that left wing parties support reforms that are inclusive in nature, while right wing parties prefer selective ones.
urn:nbn:de:101:1-201201104019
Keywords: I2; 330; education; institutions; reform; family background; Bildungsreform; Institutioneller Wandel; Bildungsverhalten; Bildungsniveau; Europa